Inverted formins: A subfamily of atypical formins. Issue 11 (29th September 2017) - Hegsted, Anna; Yingling, Curtis V.; Pruyne, David
Abstract: Formins are a family of regulators of actin and microtubule dynamics that are present in almost all eukaryotes. These proteins are involved in many cellular processes, including cytokinesis, stress fiber formation, and cell polarization. Here we review one subfamily of formins, the inverted formins. Inverted formins as a group break several formin stereotypes, having atypical biochemical properties and domain organization, and they have been linked to kidney disease and neuropathy in humans. In this review, we will explore recent research on members of the inverted formin sub‐family in mammals, zebrafish, fruit flies, and worms.